Sugar and spite - Villanueva, Gail D. (Scholastic Press, 2021)
"Jolina can't take Claudine's bullying any longer! The taunts and teasing are too much. Though Jolina knows she's still in-training to use her grandfather's arbularyo magic, she sneaks into his potions lab to get her revenge. Jolina brews a batch of gayuma, a powerful love potion. And it works. The love potion conquers Claudine's hateful nature. In fact, Claudine doesn't just stop bullying Jolina -- now she wants to be Jolina's BFF, and does everything and anything Jolina asks. But magic comes with a cost, and bad intentions beget bad returns. Controlling another person's ability to love -- or hate -- will certainly have consequences. The magic demands payment, and it is about to come for Jolina in the form of a powerful storm..."--Amazon.com